Immune Signatures Combined With BRCA1-Associated Protein 1 Mutations Predict Prognosis and Immunotherapy Efficacy in Clear Cell Renal Cell Carcinoma - Gao, Ze; Chen, Junxiu; Tao, Yiran; Wang, Qiong; Peng, Shirong; Yu, Shunli; Zeng, Jianwen; Li, Kaiwen; Xie, Zhongqiu; Huang, Hai (Frontiers in Cell and Developmental Biology, 2021)
Immunotherapy is gradually emerging in the field of tumor treatment. However, due to the complex conditions in the tumor microenvironment, some patients cannot benefit from immunotherapy. Therefore, we conducted a comprehensive analysis of the TME and gene mutations of ccRCC, hoping to find a comprehensive index that could more accurately guide the immunotherapy of patients with ccRCC. We divided ccRCC patients into two groups based on immune infiltration activity. Then, we investigated the differentially expressed genes (DEGs) and constructed a prognostic immune score using univariate Cox regression analysis, unsupervised cluster analysis, and principal component analysis (PCA), and validated its predictive power in both internal and total sets. Subsequently, the gene mutations in the groups were investigated, and the patients suitable for immunotherapy were selected in combination with the immune score. The prognosis of the immune score low group was significantly worse than the immune score high group. The mutation of BAP1 made the prognosis of the patients worse. The results of this study indicated that the establishment of an immune score model combined with BAP1 mutation could better predict the prognosis of patients, screen suitable ccRCC patients for immunotherapy, and select more appropriate drug combinations.